Bone Mineral Status in Children and Adolescents with Klinefelter Syndrome - Stefano Stagi; Mariarosaria Di Tommaso; Cristina Manoni; Perla Scalini; Francesco Chiarelli; Alberto Verrotti; Elisabetta Lapi; Sabrina Giglio; Laura Dosa; Maurizio de Martino (International Journal of Endocrinology)
Objective. Klinefelter syndrome (KS) has long-term consequences on bone health. However, studies regarding bone status and metabolism during childhood and adolescence are very rare. Patients. This cross-sectional study involved 40 (mean age: 13.7±3.8 years) KS children and adolescents and 80 age-matched healthy subjects. For both patient and control groups, we evaluated serum levels of ionised and total calcium, phosphate, total testosterone, luteinising hormone, follicle stimulating hormone, parathyroid hormone (PTH), 25-hydroxyvitamin D (25(OH)D), 1,25-dihydroxyvitamin D, osteocalcin, bone alkaline phosphatase, and urinary deoxypyridinoline concentrations. We also calculated the z-scores of the phalangeal amplitude-dependent speed of sound (AD-SoS) and the bone transmission time (BTT). Results. KS children and adolescents showed significantly reduced AD-SoS (p<0.005) and BTT (p<0.0005) z-scores compared to the controls. However, KS patients presented significantly higher PTH (p<0.0001) and significantly lower 25(OH)D (p<0.0001), osteocalcin (p<0.05), and bone alkaline phosphatase levels (p<0.005). Interestingly, these metabolic bone disorders were already present in the prepubertal subjects. Conclusions. KS children and adolescents exhibited impaired bone mineral status and metabolism with higher PTH levels and a significant reduction of 25-OH-D and bone formation markers. Interestingly, this impairment was already evident in prepubertal KS patients. Follow-ups should be scheduled with KS patients to investigate and ameliorate bone mineral status and metabolism until the prepubertal ages.